To See Is to Know: Simultaneous Display of Market Data for Retail Investors - Benamar, Hedi (Review of Finance, 2019)
Abstract I test whether the display format of market data affects the trading performance and behavior of retail investors. To do so, I exploit a large brokerage dataset covering a period during which the market information provided to the broker’s customers changed in format, but not in content. I find that a simultaneous display of cross-stock market data reduces the cognitive cost of monitoring the market and thus helps investors obtain better execution prices. In particular, investors better mitigate non-execution and adverse-selection risks when trading with limit orders. Hence, the display format of market data matters for the individual investor.